Identity in the shadow of a giant : how the rise of China is changing Taiwan - Gartner, Scott Sigmund, 1963-; Huang, Chin-Hao; Li, Yitan; James, Patrick (Bristol University Press, 2021)
This co-authored book examines the implications of the global ascent of China on cross-Strait relations and the identity of Taiwan as a democratic state, offering insights into policies for peaceful relations and prosperity across the Taiwan Strait.